Lead optimization attrition analysis (LOAA): a novel and general methodology for medicinal chemistry. Issue 8 (August 2015) - Munson, Mark; Lieberman, Harvey; Tserlin, Elina; Rocnik, Jennifer; Ge, Jie; Fitzgerald, Maria; Patel, Vinod; Garcia-Echeverria, Carlos
Highlights Attrition rate difference not readily anticipated based on individual parameters. Differentiation of series was significant when ADME parameters were included. Percentage versus compound numbers meeting criteria provided graphical overview. Steep decline (0 of 493 compounds) meeting 17/28 parameters – Series A fragile. Shallow decline (21 of 504 compounds) meeting 17/28 parameters – Series B robust.